Therapy With Cryopreserved and Lyophilized Cord Blood Leukoconcentrates in Experimental Atopic Dermatitis - Koval, Hanna; Lutsenko, Olena; Bondarovych, Mykola; Grisha, Igor; Sokil, Larysa; Ostankov, Maksym; Goltsev, Anatoliy (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2024; 34(4):282–286